Clinical Application of Chinese Herbal Injection for Cancer Care: Evidence-Mapping of the Systematic Reviews, Meta-analyses, and Randomized Controlled Trials - Yang, Ming; Zhu, Si-jia; Shen, Chen; Zhai, Rui; Li, Duo-duo; Fang, Min; Xu, Jing-nan; Gan, Ye-na; Yang, Lu; Ren, Zhi-ying; Zheng, Ruo-xiang; Robinson, Nicola; et al. (Frontiers in Pharmacology, 2021)
Background and objective: Cancer is a life threatening disease worldwide. The standard therapy cannot fulfill all the clinical needs and Chinese herbal injections have been widely used for cancer in Chinese and Western hospitals in China. This study aims to apply evidence mapping to draw an overview picture of the clinical application of Chinese herbal injections in cancer care based on randomized controlled trials, systematic reviews and meta-analyses. Methods and results: Seven databases were systematically searched, eligible randomized controlled trials, systematic reviews and meta-analyses on one type of the nine Chinese herbal injection for cancer covered in the national essential health insurance program were included. Excel 2016 and RStudio were used to integrate and process the data. In total 361 randomized controlled trials, 48 systematic reviews and meta-analyses were included in the evidence mapping, including Compound kushen, Shenqi fuzheng, Aidi, Kangai, Kanglaite, Xiaoaiping, Cinobufacin, Brucea javanica oil emulsion and Polyporus polysaccharide injection. The health insurance restricted the scoping of clinical application for nine herbal injections. The numbers of studies increased especially around 2013-2015. The most studied cancer types were lung cancer (116, 32.1%), colorectal cancer (39, 10.8%) and gastric cancer (39, 10.8%), and the most used injections were Compound kushen (78, 21.6%), Shenqi fuzheng (76, 21.1%), and Aidi (63, 17.5%) in randomized controlled trials. The most consistently reported benefits were observed in Compound kushen, Shenqi fuzheng, Aidi and Kangai for outcomes including tumor response, quality of life, myelosuppression, and enhancing immunity. Conclusion: The current evidence mapping provides a visual overview of the outcomes and effects for Chinese herbal injections in cancer care, and offers clinical application information to warrant further evidence-based research in order to inform clinical and policy decision-making.